Tight Binding Inhibitors of Scytalone Dehydratase: Effects of Site-Directed Mutations - Jordan, Douglas B; Basarab, Gregory S; Steffens, James J; Schwartz, Rand S; Doughty, James G (Biochemistry (Easton), 2000)
We explore the use of site-directed mutations of scytalone dehydratase to study inhibitor binding interactions. The enzyme is the physiological target of new fungicides and the subject of inhibitor design and optimization. X-ray structures show that potent inhibitors (K i's ≈ 10-11 M) interact mostly with 11 amino acid side chains and, in some cases, with a single backbone amide. Fifteen site-directed mutants of the 11 enzyme residues were prepared to disrupt enzyme−inhibitor interactions, and inhibition constants for 13 inhibitors were determined to assess changes in binding potencies. The results indicate that two of the six hydrogen bonds (always present in X-ray structures of native enzyme−inhibitor complexes) are not important for inhibitor binding. The other four hydrogen bonds are important for inhibitor binding, and the strength of the individual bonds is inhibitor-dependent. Inhibitor atoms remote from the hydrogen bonds influence their strength, presumably by effecting small changes in inhibitor orientation. Several hydrophobic amino acid residues are important recognition elements for lipophilic inhibitor functionalities, which is fully consistent with X-ray structures determined from crystals of enzyme−inhibitor complexes grown at neutral pH but not with those determined from crystals grown under acidic conditions. This study of mutant enzymes complements insights from X-ray structures and structure−activity relationships of the wild-type enzyme for refining views of inhibitor recognition.